Relationship between Social Support and Career Maturity of Class XII Students of SMKS Al Mahrusiyah Lirboyo Kediri City: Hubungan antara Dukungan Sosial dengan Kematangan Karir Siswa Kelas XII SMKS Al Mahrusiyah Lirboyo Kota Kediri - Ahmad Nur Azhar; Beti Malia Rahma Hidayati (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Vocational high schools (SMK) are educational institutions designed to produce graduates who are mature and ready to face the world of work. However, several factors that cause the increase in the level of career maturity of students are a consideration that must be considered. The purpose of this study was to determine the level of relationship between social support and career maturity and to determine whether there is a significant relationship between social support and career maturity of class XII students of SMKS Al-Mahrusiyah Lirboyo Kediri City. This study uses quantitative methods with inferential statistical data analysis techniques. the sample of this study amounted to 77 students using purposive random sampling technique. The data analysis technique uses Spearman's Rho correlation using the help of the IBM SPSS Statistic version 25 application. Based on the results of the study found that the average grade XII student of SMKS Al-Mahrusiyah Lirboyo Kota Kediri has a level of social support in the moderate category with a percentage of 77% as many as 59 students, and a level of career maturity in the moderate category with a percentage of 74% as many as 57 students, with a significance of 0.000 <0.05, it can be concluded that there is a significant positive relationship between social support and career maturity. The correlation between social support and career maturity is 0.557, which means the relationship is strong.